Integrating Global Citizenship Education into Language Learning to Foster Intercultural Awareness among Secondary School Students - Arjulayana Arjulayana; Desmaliza Desmaliza; Rachmi Rachmi (Global Education : International Journal of Educational Sciences and Languages, 2024)
This study examines the integration of Global Citizenship Education (GCE) into language learning and its effects on secondary school students' intercultural sensitivity, global perspectives, and critical thinking. As globalization expands, education systems must not only develop linguistic skills but also prepare students to engage with global challenges and diverse cultures. A mixed methods approach was used, incorporating surveys, reflective journals, and classroom observations to assess how GCE influences students' understanding of global issues and cultural diversity. Results show that GCE integration significantly enhances students' intercultural sensitivity and global awareness, equipping them to navigate cross-cultural interactions. Students also demonstrated improved critical thinking skills, especially in analyzing global issues and engaging with intercultural viewpoints. The study emphasizes the importance of collaborative learning, such as Collaborative Online International Learning (COIL), in fostering intercultural empathy and global citizenship skills. It suggests that language educators should integrate GCE themes to develop globally conscious and interculturally aware students. Further research is needed to explore the long-term effects of GCE on language learners and its application in various educational settings. By providing students with the tools to tackle global challenges, GCE can play a crucial role in shaping responsible, globally aware citizens.